Expression of HMGB1 and NF-κB in Fetal Membranes of Premature Rupture of Membranes - Sudiarta, Ketut Edy; Khan, Joan; Aldinasyah, Monicha Zalzabilla; Garianto, Efyluk; Budiarti, Retno (Althea Medical Journal, 2023)
Background: Inflammation, either sterile or infection-related, may lead to premature rupture of membranes (PROM). The non-histone nuclear proteins, high mobility group box-1 (HMGB1), and nuclear factor kappa-B (NF-κB) transcription factors have been extensively investigated in many disorders involving inflammatory reactions. This study aimed to determine the expression of HMGB1 and NF-κB in fetal membranes of PROM compared with non-PROM.Methods: This study was an analytical observational study with a case-control design, performed from November 2021 to January 2022, including 40 fetal membrane samples (20 PROM and 20 non-PROM), which were obtained from pregnant women treated in the emergency unit of a hospital in Surabaya from August to November 2019 using the non-probability sampling method. The HMGB1 and NF-κB expressions were examined using the immunohistochemical method and further viewed under a light microscope (400x magnification), then assessed by Image-J software. The values were then compared between PROM and non-PROM, and analyzed using the Mann-Whitney U test.Results: There was a significant difference (p<0.001) in the expression of HMGB1 and NF-κB in PROM and non-PROM for HMGB1 45.86± 14.21% vs. 8.50± 5.66% expression/mm2; and NF-κB 33.47±5.45% vs. 7.29±4.90% expression/mm2, respectively.Conclusions: PROM groups have significantly higher expression of HMGB1 and NF-κB s, indicating their higher activity and contribution to PROM.